¿Incide la ISO 14000 en el desempeño exportador de las empresas colombianas? - Claudia Paola García-Castiblanco; Diana Marcela Díaz-Ariza; Carlos Andrés Pinzón-Muñoz (CLIO América, 2019)
The environmental management systems, which are certified by the Standardization International organization -ISSO 14000, are in the search to ensure the appropriate resources management of enterprises to determine environmentally friendly conditions. Be able to fulfill the international standards and thus rendering access to international markets is thereason why factories develop certification process. Colombia is one of the countries where the ISSO 14000 norm has been adopted but, it is worth asking if this process spawn increase exportation volume. For the implementation of this research, the export performance was analyzed between exporting and certified markets and non-certified ones through a parametric hypothesis test. As a result, it was identified that there is a significant difference between the number of exportations by certified markets than the ones that are not. However, the study does not state that the abroad sales leverage is because of ISO 14000.